Health Literacy of Pacific Mothers in New Zealand Is Associated with Sociodemographic and Non-communicable Disease Risk Factors: Surveys, Focus Groups and Interviews - Sa'uLilo, Losi; Tautolo, El-Shadan; Egli, Victoria; Smith, Melody (Pasifika Medical Association, 2018)
Introduction: Pacific people living in New Zealand, suffer from inequitably high rates of non-communicable diseases and their associated risk factors. This disease burden may be compounded by low health literacy levels. The objectives of this research were: (1) measure relationships between health literacy, socio-demographic factors and non-communicable disease risk factors in a large sample of Pacific mothers living in New Zealand and (2) gain in-depth understanding of social and cultural factors contributing to these relationships. Methods: Logistic regression was employed to investigate health literacy and: acculturation, socioeconomic status, physical activity, education, smoking status, health status, and alcohol consumption. Semi-structured focus groups were conducted with Pacific mothers and interviews with Pacific health professionals adopting the culturally appropriate talanoa, and kakala methods, within the Fonofale framework. Findings: Associations between low health literacy and age, ethnicity, acculturation, employment, education, smoking status, and alcohol status were shown. Novel findings from the focus groups were: the use and comprehension of health information and what constitutes preferred information and health service delivery modes. Conclusions: Findings suggest current health related information is not being used to its fullest extent by Pacific mothers. This may be due to underlying socio-demographic factors. This is the first study to examine the factors related to health literacy among Pacific mothers in NZ. Findings should be used to inform future interventions and delivery of public health nutrition messages.
Keywords: 4203 Health Services and Systems; 4206 Public Health; 42 Health Sciences; Behavioral and Social Science; Prevention; Alcoholism, Alcohol Use and Health; Substance Misuse; Basic Behavioral and Social Science; 3.1 Primary prevention interventions to modify behaviours or promote wellbeing; 2 Aetiology; 3 Prevention of disease and conditions, and promotion of well-being; 2.3 Psychological, social and economic factors; Cardiovascular; Generic health relevance; 3 Good Health and Well Being